The impact of learning disabilities on children and parental outcomes: Evidence from the Panel Study of Income Dynamics - Rachel Cummings; Maria José Luengo-Prado (Federal Reserve Bank of Boston, 2023)
We document the characteristics of children and young adults identified in the Panel Study of Income Dynamics as having a learning disability and study whether legislative changes in diagnosis criteria have had a noticeable effect determining who receives a diagnosis. We further document that children and young adults identified as a having a learning disability experience less desirable outcomes early in life, including trouble with the police, drug use, violent behavior, incarceration, self-reported low levels of well-being, lower educational attainment, and less favorable labor market outcomes. We also find that the mothers of children diagnosed with learning disabilities are less likely than other mothers to participate in the labor market.
Keywords: J24; I24; 330; learning disabilities; young adult outcomes; labor market outcomes